PERGANTIAN AUDITOR DAN KOMITE AUDIT TERHADAP KUALITAS AUDIT DENGAN PERUBAHAN MANAJEMEN SEBAGAI VARIABEL MODERASI - Maharani, Destin Alfianika; Tyas, Karunia Zuraidaning; Amelia, Shella Rizqi; Fitriyanti, Fitriyanti Alfianika (JURNAL AKUNTANSI, 2025)
Financial reports as a form of company accountability to stakeholders related to the company's operations during a period require competent and independent external parties. External parties that can be used by the company are external auditors or public accountants or KAP auditors. The use of external auditors will later provide opinions on financial reports based on the auditor's code of ethics and work standards. In selecting external auditors, there are various factors that can influence, for example company policies and government regulations. This study aims to determine the effect of changing auditors and audit committees on audit quality with management changes as a moderating variable. After data analysis, the results obtained were that changes in auditors and audit committees had a positive effect on audit quality, changes in management had no effect on audit quality. Meanwhile, changes in management as a moderating variable obtained the results that changes in management can be used as a moderating variable between the audit committee and audit quality, while changes in management were not proven to moderate the effect of changes in auditors on audit quality.